Omega 3 Fatty Acids Reduce Bone Resorption While Promoting Bone Generation in Rat Apical Periodontitis - Azuma, Mariane Maffei [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Ervolino, Edilson [UNESP]; Pipa, Camila Barbosa [UNESP]; Cardoso, Carolina de Barros Morais [UNESP]; Andrada, Ana Cristina; Kawai, Toshihisa; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier, 2017)
Introduction This study evaluated the effects of the dietary supplement omega 3 polyunsaturated fatty acids (ω-3 PUFAs) on pulp exposure–induced apical periodontitis (AP) in rats. Methods Twenty-eight male rats were divided into groups: control untreated rats (C), control rats treated with ω-3 PUFAs alone (C-O), rats with pulp exposure–induced AP, and rats with pulp exposure–induced AP treated with ω-3 PUFAs (AP-O). The ω-3 PUFAs were administered orally, once a day, for 15 days before pulp exposure and, subsequently, 30 days after pulp exposure. Rats were killed 30 days after pulp exposure, and jaws were subjected to histologic and immunohistochemical analyses. Immunohistochemical analyses were performed to detect tartrate-resistant acid phosphatase–positive osteoclasts and osteocalcin-positive osteoblasts on the bone surface of periapical area. Results were statistically evaluated by using analysis of variance and Tukey honestly significant difference, and P <.05 was considered statistically significant. Results The bone resorption lesion was significantly larger in the AP group compared with AP-O, C, and C-O groups (P <.05). The level of inflammatory cell infiltration was significantly elevated, and the number of tartrate-resistant acid phosphatase–positive osteoclasts was significantly higher in the periapical lesions of the AP group compared with AP-O, C, and C-O groups (P <.05). The number of osteocalcin-positive osteoblasts was significantly increased in the AP-O group compared with the AP group (P >.05). Conclusions Supplementation with ω-3 PUFAs not only suppresses bone resorption but also promotes new bone formation in the periapical area of rats with AP in conjunction with downregulation of inflammatory cell infiltration into the lesion.
Keywords: Apical periodontitis; endodontic infection; omega 3 fatty acids; osteocalcin